Istrātījiyyah Taʿlīm al-Lughah al-ʿArabiyyah al-Faʿʿālah fī Maʿmal al-Lughah li-Ṭalabah Maʿhad Dār al-Salām Kuntūr Fūnūrūkū - Alif Cahya Setiyadi (Lisanudhad: Jurnal Bahasa, Pembelajaran dan Sastra Arab, 2014)
Language education scholars agree that one of the primary goals of language teaching is to enable students to speak the language fluently and develop proficiency in listening, reading, and writing. To achieve this objective, language teachers today require advanced instructional media, one of which is the language laboratory. Darussalam Gontor Islamic Boarding School has utilized a language laboratory to enhance its students’ Arabic proficiency and to serve as an effective medium for teaching language skills through specialized instructional strategies. These strategies are designed to encourage students to apply correct grammatical structures by listening to authentic Arabic and English spoken by native speakers. The implementation of these strategies is adapted to students’ proficiency levels, which are classified into three categories: beginner, intermediate, and advanced.